1989
DOI: 10.1162/jocn.1989.1.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Brainprints: Computer-Generated Two-Dimensional Maps of the Human Cerebral Cortex in vivo

Abstract: We describe an in vivo method for the quantitative analysis of human necrotical anatomy. The technique allows unfolded regions of functional and morphological interest to be measured planimetrically. Two-dimensional cortical maps and surface area determinations derived from magnetic resonance images of monozygotic twins are presented. In addition, reconstructions and measurements of published post-mortem human and rhesus monkey hemispheres are reported. Potential applications for the study of brain organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 47 publications
1
27
1
1
Order By: Relevance
“…The total cortical surface area of 1570 cm 2 for both hemispheres is similar to the estimate of Jouandet et al (1989). It is ϳ20% lower than the mean reported by Tramo et al (1995), but the real difference is probably smaller, because our value is likely to be a slight underestimate (see Materials and Methods).…”
supporting
confidence: 76%
“…The total cortical surface area of 1570 cm 2 for both hemispheres is similar to the estimate of Jouandet et al (1989). It is ϳ20% lower than the mean reported by Tramo et al (1995), but the real difference is probably smaller, because our value is likely to be a slight underestimate (see Materials and Methods).…”
supporting
confidence: 76%
“…The brainprint, introduced by Jouandet et al (1989), was developed from 42 contiguous, T1 coronal, 3.8-mm MRI slices of the cerebrum (Fig. 5).…”
Section: Future Anatomical Study Of Central Deafnessmentioning
confidence: 99%
“…Willerman and Schultz (1996) suggested that cortical area might be a good index based on the studies of Jouandet et al (1989) and Tramo et al (1995). Eysenck (1982) provided an excellent earlier review.…”
Section: Selection and Cognitive Abilitymentioning
confidence: 99%